The plant lipid contactome: emerging roles of inter-organelle contact sites in lipid metabolism - Huércano Rubens, Carolina; Moya-Barrientos, Miriam; Cuevas Corral, Oliver; Cárdenas, Carlos; Salas, Joaquín J.; Sanchez-Vera, Victoria; Ruiz-López, Noemí (Elsevier, 2026)
Membrane contact sites (MCSs) are fundamental hubs of inter-organelle communication that mediate the non-vesicular exchange of lipids, ions, and metabolites, thereby sustaining cellular homeostasis. In plants, the “contactome”—the dynamic network of all membrane contact sites—has evolved distinctive features to accommodate the requirements of a sessile, photosynthetic lifestyle and the presence of plastids. Within this network, the endoplasmic reticulum (ER) functions as a central hub for lipid biosynthesis and distribution, forming functionally important contacts with multiple organelles. Recent advances in high-resolution imaging, lipidomics, and molecular genetics are beginning to uncover the complexity of these inter-organelle connections and their contribution to lipid homeostasis in plants. This review summarizes current knowledge of the plant contactome, with a focus on lipid transfer proteins and lipid-modifying enzymes that maintain lipid balance during organelle biogenesis, plant development, and stress adaptation. Plant lipid transfer at membrane contact sites can be broadly divided into two mechanistic modes: precision-regulated “shuttles,” exemplified by the Ca2+-dependent SYT1-mediated diacylglycerol transfer at ER–plasma membrane interfaces, and high-capacity lipid transfer mechanisms, such those mediated by ATG2, that support rapid lipid flux during autophagosome biogenesis. Knowledge of lipid metabolism at plant membrane contact sites is still in its initial stages, and many of the underlying mechanisms remain unexplored. Major challenges include understanding how these sites integrate stress responses, metabolic fluxes, and organelle dynamics. Addressing these questions will be essential to unravel the unique aspects of plant lipid biology and may open opportunities for improving stress resilience and metabolic engineering in crops.
Keywords: Membranas lipídicas; Orgánulos vegetales; Ciclo vegetal celular; Membrane contact sites; Lipid metabolism; Lipid transfer proteins; Organelle communication; Non-vesicular transport; Endoplasmic reticulum; Contactome